Stabilization by Benzannulation: Butterfly Azaacenes. Issue 49 (5th August 2018) - Müller, Matthias; Reiss, Hilmar; Tverskoy, Olena; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract: Soluble butterfly‐shaped tetraazapentacenes and tetraazaheptacenes were prepared by condensation or Stille coupling with a stannafluorene. The stability of the benzo‐winged tetraazaheptacene is dramatically increased through the fourfold benzannulation, yet its acene character is retained to a significant extent. Abstract : Benzannulation meets nitrogen : Stable and soluble tetraazaacenes were π‐extended through condensation or Stille reactions with up to seven linearly annulated rings (see scheme).